2017
DOI: 10.1017/s003329171600355x
|View full text |Cite
|
Sign up to set email alerts
|

Job strain as a risk factor for clinical depression: systematic review and meta-analysis with additional individual participant data

Abstract: BackgroundAdverse psychosocial working environments characterized by job strain (the combination of high demands and low control at work) are associated with an increased risk of depressive symptoms among employees, but evidence on clinically diagnosed depression is scarce. We examined job strain as a risk factor for clinical depression.MethodWe identified published cohort studies from a systematic literature search in PubMed and PsycNET and obtained 14 cohort studies with unpublished individual-level data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
284
6
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(336 citation statements)
references
References 63 publications
18
284
6
9
Order By: Relevance
“…Baseline sub-clinical depressive symptoms would be confounders, if they caused both over-reporting of ERI at baseline and onset of depressive disorders at followup, but they would be mediators if ERI before baseline caused baseline sub-clinical depressive symptoms, which subsequently caused onset of depressive disorders at follow-up. A recent study on job strain and hospital treatment for depressive disorders showed reciprocal associations between job strain and sub-clinical depressive symptoms, suggesting that depressive symptoms are both confounders and mediators for the association of job strain and depressive disorders (58). If this reciprocal association is also true for ERI and sub-clinical depressive symptoms, then the association of ERI and risk of depressive disorders would be underestimated by adjusting and overestimated by not adjusting for subclinical depressive symptoms.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…Baseline sub-clinical depressive symptoms would be confounders, if they caused both over-reporting of ERI at baseline and onset of depressive disorders at followup, but they would be mediators if ERI before baseline caused baseline sub-clinical depressive symptoms, which subsequently caused onset of depressive disorders at follow-up. A recent study on job strain and hospital treatment for depressive disorders showed reciprocal associations between job strain and sub-clinical depressive symptoms, suggesting that depressive symptoms are both confounders and mediators for the association of job strain and depressive disorders (58). If this reciprocal association is also true for ERI and sub-clinical depressive symptoms, then the association of ERI and risk of depressive disorders would be underestimated by adjusting and overestimated by not adjusting for subclinical depressive symptoms.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…This disorder is linked to a reduction in the quality of life, premature retirement, and more years with disability (3). With regard to its causes, depression is known to be a multifactorial disorder with biological, environmental, and psychological factors involved in its development (4)(5)(6)(7)(8), including psychosocial work stressors (9)(10)(11). To date, most studies have investigated the association between psychosocial work stressors and depression measuring work stressors according to the models of effort-reward imbalance (ERI) and job strain.…”
mentioning
confidence: 99%
“…ERI is based on the notion of failed contractual reciprocity between efforts spent and rewards received at work, where rewards include money, promotion prospects, job security, and esteem (13). The majority of these studies suggest that ERI and job strain or specific components of these stressors are related to the onset of depression (9,10,14).…”
mentioning
confidence: 99%
“…CHD, depression) (e.g. Kivimäki, Nyberg, & Batty, 2012;Madsen et al, 2017). Researchers who are sympathetic to Karasek's model have pointed out that these meta-analyses have many methodological problems.…”
Section: Editorialmentioning
confidence: 99%